DETERMINAN PERTUMBUHAN EKONOMI - ., Suyanto; Widiana, Anika (Journal of Management and Business, 2007)
This study examines the determinants of Growth in Indonesia using time series data from the first quarter of 1980 to fourth quarter of 2000. The result of OLS regression model shows that labor, physical capital, human capital, openness, and an institutional factor give positive effects to economic growth in Indonesia. This finding supports the arguments presented by neo-classical economists. The effect of institutional variable (e.g. inflation), in particular, exhibit the intervention of the central bank and the government in inflation and economic growth. Since the estimators consist of autocorrelation, the stationary test is applied to test the integration degrees and co-integration methodology is adopted to examine the linear combination of selected variables. The Granger’s two step error correction model tells us that the short-run disequilibrium is divergent from time to time from the long-run equilibrium, with the moderate speed of divergence. However, at least the long-run OLS estimators are unbiased, consistent, and asymptotically normally distributed.